United Republic of Tanzania : 2007 Article IV Consultation and First Review Under the Policy Support Instrument; Staff Report; Staff Supplement; Public Information Notice and Press Release on the Executive Board Discussion; and Statement by the Executive Director for the United Republic of Tanzania. (IMF Staff Country Reports; Country Report ;, 2007)
This paper discusses the United Republic of Tanzania's 2007 Article IV Consultation and First Review under the Policy Support Instrument. The report focuses on sustaining Tanzania's recent strong economic performance, broad-based growth, and more rapid poverty reduction. This would require maintaining the structural reforms momentum through measures that enhance public resource mobilization and efficiency of spending and increase the financial sector's contribution to growth. The authorities are taking steps to alleviate key bottlenecks constraining economic activity, notably by improving infrastructure and enhancing the business environment.